2019
DOI: 10.1183/16000617.0111-2018
|View full text |Cite
|
Sign up to set email alerts
|

Dismantling the pathophysiology of asthma using imaging

Abstract: Asthma remains an important disease worldwide, causing high burden to patients and healthcare systems and presenting a need for better management and ultimately prevention and cure. Asthma is a very heterogeneous condition, with many different pathophysiological processes. Better measurement of those pathophysiological processes are needed to better phenotype disease, and to go beyond the current, highly limited measurements that are currently used: spirometry and symptoms. Sophisticated three-dimensional lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 106 publications
0
22
0
Order By: Relevance
“… 13 , 14 During an allergic reaction, these cells trigger smooth muscle contraction in the airways, microvascular leakage, and airway mucus secretion. 15 , 16 …”
Section: Introductionmentioning
confidence: 99%
“… 13 , 14 During an allergic reaction, these cells trigger smooth muscle contraction in the airways, microvascular leakage, and airway mucus secretion. 15 , 16 …”
Section: Introductionmentioning
confidence: 99%
“…1 ). We categorized these patterns according to the descriptions in the previous studies ( 13 14 15 17 18 ). If one patient had any two or three intermixed ventilation patterns, the most predominant pattern was used to describe the abnormality.…”
Section: Methodsmentioning
confidence: 99%
“…In asthma it was shown that the airway walls, as measured on CT, were thicker compared to healthy subjects. Furthermore, it was shown that increased airway wall thickness observed on CT was related to lower forced expiratory volume in 1 s and higher risk of exacerbations [138,140]. Static CT images acquired during expiration can show regions of low attenuation that are thought to reflect SAD (figure 2).…”
Section: Static Imagingmentioning
confidence: 99%
“…An in-depth review by KING et al [140], reported important findings on CT and three-dimensional ventilation imaging in the large airways, small airways and the parenchyma of patients with asthma. In that review, KING et al [140] further elaborate on the current and possible future use of different imaging modalities to improve our understanding of the role of small airways in asthma pathophysiology and on what further research is needed.…”
Section: Dynamic Imagingmentioning
confidence: 99%